2018
DOI: 10.1177/0300891618765541
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and brain metastases: An aggressive disease with a different response to treatment

Abstract: CRC with BM is an aggressive disease resistant to standard treatment and is associated with poor outcomes. Adding antiangiogenic therapy might be of value for those patients. Patients with BM developing early in the disease course might respond better to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Overall, 541,244 CRC cases were included, involving 1547 patients diagnosed with BM [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The overall average incidence of BM in CRC patients was 2.10% (95%CI 0.98–3.22) ranging from 0.1% up to 11.5% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Fifty-seven percent of patients were male and 43% were female ( Figure 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 541,244 CRC cases were included, involving 1547 patients diagnosed with BM [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The overall average incidence of BM in CRC patients was 2.10% (95%CI 0.98–3.22) ranging from 0.1% up to 11.5% [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Fifty-seven percent of patients were male and 43% were female ( Figure 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The smallest study population reported on five patients, while the largest study included 475 patients with BM. The analyzed studies are shown in Figure 6 and Table 7 [ 9 , 10 , 11 , 12 , 14 , 15 , 18 , 20 , 23 , 24 , 25 , 26 , 27 , 29 , 34 , 45 , 46 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced stage melanoma patients had a similar 50% risk [7]. In contrast, brain metastases developed in only about 2% of cases with renal cell carcinoma and colorectal cancer [8,9]. Nowadays, in order to achieve durable control of brain disease, minimize the early and late adverse effects of therapy and maintain quality of life, surgery and radiotherapy are the treatment of choice.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of patients with CRC has greatly improved with the advancement of multimodality treatment. However, the prognosis remains poor for patients at late stages (clinical stages III and IV) since these patients present tumor metastasis and poor response to treatment ( 2 , 3 ). Unfortunately, many patients with CRC are diagnosed at the advanced stage.…”
Section: Introductionmentioning
confidence: 99%